Melanic familial nevus. - Garofalo, L.; Bonifazi, E. (European Journal of Pediatric Dermatology, 2007)
Dermoscopy can be useful in differentiating congenital melanocytic nevus from hypermelanic nevus, the latter being devoid of cells and thus not prone to degeneration.